Intellectual Property Rights and Scientific Plagiarism - Salma Antar Shadofa (International Journal of Law Research and Studies, 2024)
Intellectual property is a legal right that a particular entity owns over the creative works it produces, such as inventions, symbols, industrial models, images, artistic and literary works, and names. These works may be produced by the entity itself or transferred to its ownership later. Intellectual property requires legal protection to prevent theft, fraud, or forgery. Intellectual property rights are numerous and include several types, including: copyrights, patents, trademarks, in addition to industrial designs, geographical indications, and trade secrets. Intellectual property protection contributes to enhancing creativity and encouraging innovation, as it guarantees inventors and companies full benefit from their inventions. This incentive prompts them to focus more on research and development. In addition, intellectual property rights protect products from unfair competition and provide a source of income through the sale or licensing of the use of these rights. Finally, intellectual property rights can be used as a guarantee to obtain financing. This research presents the most important concepts in this field and how they are linked to scientific thefts.